Study of Thermal Energy Production by Combustion of Lard and Diesel Mixtures - J. F. San José Alonso; S. Alonso Miñambres; I. Gobernado Arribas (Journal of Combustion)
This work presents the experimental results of lard combustion with diesel for heating. The work is divided into two parts, the first of which deals with the identification of lard as fuels and characterization of diesel, as well as determining the chemical and thermodynamic properties of mixtures of both components. The second part studies the optimum combustion point of lard and oil mixtures in a conventional plant, varying the percentage of lard in mixing, air flow, and injection pressure.